Binary Fe-Pd submicron structures fabricated through glancing angle deposition (GLAD) for bioapplications. (5th October 2017) - Allenstein, Uta; Wisotzki, Emilia I.; Gräfe, Christine; Clement, Joachim H.; Liu, Yanhui; Schroers, Jan; G. Mayr, Stefan
Abstract: Fe7 Pd3 structured thin films were synthesized using GLAD, motivated by the high potential of such structures in magnetically-controlled bioapplications. GLAD was carried out on prestructured gold templates to obtain Fe-Pd structures of several hundred nanometers in width by up to 1.5 μm in length, depending on template and growth parameters. The resulting polycrystalline microstructure was in the body centred cubic (bcc) phase with a composition near Fe7 Pd3, determined by energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD). Annealing at 900 °C resulted in the appearance of signatures of the face centred tetragonal (fct) martensitic phase within XRD measurements. Therefore, fct structures could be achieved if measures for structural preservation are taken, such as by ultra rapid annealing or lift-off before annealing. The cellular response to the structured films was investigated using human brain microvascular endothelial cells (HBMEC) and revealed consistent cell adhesion, morphologies and proliferation compared to control Fe-Pd and Si substrates. Only trace amounts of palladium and iron were released from the films into the growth medium during culture, regardless of the structures. Overall, this method is highly promising for the development of biocompatible, submicron structured films and shape-anisotropic ferromagnetic micro- and nanostructures, with applicability to a range of other alloys. Graphical abstract: Highlights: Glancing angle deposition (GLAD) was used to synthesize Fe-Pd submicron structures. Prestructured substrates were used as seeds to direct the Fe-Pd deposition. Submicron structures had consistent biocompatibility in comparison to unstructured Fe-Pd. Such shape-anisotropic magnetic structures have significant bioapplications. This technique should be applicable to a range of other alloys.